Combined effect of nutrient and flashing light frequency for a biochemical composition shift in Nannochloropsis gaditana grown in a quasi‐isoactinic reactor. (19th May 2020) - Lima, Serena; Villanova, Valeria; Grisafi, Franco; Brucato, Alberto; Scargiali, Francesca
Abstract: Artificial lighting may be an interesting opportunity for the cultivation of microalgae as an alternative to natural sunlight. In particular, light emitting diodes (LEDs) can be employed to tailor the lighting to the microalgal culture in a controlled mode in order to create flashing light. In order to establish the effect of the flashing frequency on growth and biochemical composition of a model microalga, a quasi‐isoactinic reactor, in which the light distribution is almost homogeneous, was set up. In this work, it was employed for the cultivation of the heterokont Nannochloropsis gaditana in two growth media with limiting and nonlimiting nutrients. The combined effect of nutrient concentration and flashing frequency on the growth, lipid content, fatty acid content, and pigment content was assessed for the first time. The results indicate that both nutrient concentration and flashing frequency influence the above‐mentioned parameters. In particular, under flashing light conditions, an increase of lipid content and a decrease of polyunsaturated fatty acids (PUFAs) and chlorophyll are observed when nutrients are deficient, while the opposite effects are shown when nutrients are abundant.